Early Lung Function and Future Asthma - Sánchez-Solís, Manuel (Frontiers in Pediatrics, 2019)
Asthmatic adults with lower lung function have been described as having had this worse condition early in life. Lung function is reduced in children with persistent asthma and continues low throughout adult life. The challenge is to know if impaired lung function is a risk factor of asthma, as a consequence of special congenital characteristics of the airways, or whether asthmatic patients suffer a loss in lung function as early as nine years of age as a consequence of very precocious remodeling of the airways. The loss is so early in life that it is probably a congenital characteristic, however there is not a cut-off point with clinical interest to predict risk of asthma later in life. There are contradictory results regarding whether asthmatic children lose lung function as a consequence of the airway remodeling by the illness itself. This aspect seemed to be shown for children at risk - the offspring of asthmatic mothers. The early BHR seems to be very frequent even in healthy infants, but is probably not a risk factor for asthma years later; except in the offspring of asthmatic mothers in which it has been shown. There are still many uncertainties in this field; so, more research is needed in order to better understand the pathophysiology of asthma, the early risk factors and to design new therapeutic targets and early interventions to change the natural history of the disease.